2015
DOI: 10.1159/000433546
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Proton Beam Radiotherapy for Large Non-Peripapillary Choroidal and Ciliary Body Melanoma at TRIUMF and the BC Cancer Agency

Abstract: Background and Purpose: To report outcomes and toxicity after proton beam radiotherapy for non-peripapillary choroidal and ciliary body melanoma considered unsuitable for other eye-sparing therapies. Materials and Methods: An existing database of 77 patients with non-peripapillary tumors treated at TRIUMF, Canada, including patient, tumor, and treatment characteristics, was updated with ocular complications and follow-up status from chart reviews. Results: Most of the patients had large tumors: 61% were T3/T4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 23 publications
0
18
0
1
Order By: Relevance
“…Although technical differences leading to clinical discrepancies cannot be ignored as shown in this study, a high local tumor control of up to 95% is reported by all the institutions. [2][3][4][5][6][7][8][9][10] The distal fall-off is determined by the beam design properties and the initial energy leaving from the accelerator. The ideal scenario would be using a low-energy cyclotron dedicated to the treatment of ocular lesions resulting in the sharpest distal penumbra for all possible combinations of the RMWs and the range shifter values like in HZB-Charite, Berlin, and CAL, Nice.…”
Section: Discussionmentioning
confidence: 99%
“…Although technical differences leading to clinical discrepancies cannot be ignored as shown in this study, a high local tumor control of up to 95% is reported by all the institutions. [2][3][4][5][6][7][8][9][10] The distal fall-off is determined by the beam design properties and the initial energy leaving from the accelerator. The ideal scenario would be using a low-energy cyclotron dedicated to the treatment of ocular lesions resulting in the sharpest distal penumbra for all possible combinations of the RMWs and the range shifter values like in HZB-Charite, Berlin, and CAL, Nice.…”
Section: Discussionmentioning
confidence: 99%
“…Proton irradiations were performed at the Proton Therapy facility at TRIUMF 24 , the only Proton Therapy centre in Canada to date 25,26 , and one of several centers specializing in treating ocular cancer worldwide 27 . The facility consists of a dedicated horizontal beam line, extracting 74 MeV protons from the TRIUMF main cyclotron 28 .…”
Section: Methodsmentioning
confidence: 99%
“…It results in local control of the disease in more than 95% of cases and in a relatively high rate of eye preservation [ 66 , 67 , 68 , 69 , 70 , 71 ]. Side effects of PBR depend mainly on the size and location of the tumour [ 72 , 73 , 74 , 75 , 76 , 77 , 78 ]. Radiation keratopathy represents a possible complication after PBR occurring in 1–11.5% of cases [ 66 , 68 , 78 , 79 ].…”
Section: Radiotherapy For Uveal Melanomamentioning
confidence: 99%
“…Other complications reported following PBP include pseudophakic bullous keratopathy (2%) and dry eye disease (6%) [ 84 , 87 , 88 , 89 ]. However, most studies reported no impairment of the ocular surface [ 67 , 75 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 ]. Figure 3 shows the management of toxicity in a patient affected by large cilio-choroidal melanoma with diffuse iris invasion, treated with PBR to the entire anterior segment.…”
Section: Radiotherapy For Uveal Melanomamentioning
confidence: 99%